Study on Photoelectric Properties of Graphene/Molybdenum Disulfide Heterojunction - Hui Ren; Xing Wei; Jibin Fan (Nanomaterials)
The zero-bandgap of graphene means that it can achieve a full spectral range response for graphene-based photodetectors. But the zero bandgap of graphene also brings relatively large dark current. To improve this issue and achieve low-cost graphene-based photodetectors, radio frequency (RF) magnetron-sputtered molybdenum disulfide constructed with graphene to form heterojunction was investigated. The results indicated that graphene/molybdenum disulfide heterojunction could provide a Schottky barrier height value of 0.739 eV, which was higher than that of the graphene/Si photodetector. It is beneficial to suppress the generation of the dark current. Different sputtering conditions were also studied. Testing results indicated that for the optimized process, the responsivity, detectivity, and quantum efficiency of graphene/molybdenum disulfide heterojunction photodetectors could reach up to 126 mA/W, 1.21 × 1011 Jones, and 34%, respectively. In addition, graphene/molybdenum disulfide heterojunction on flexible PET substrate showed good stability, indicating that graphene/molybdenum disulfide heterojunction also has a good potential application in the field of flexible electronics.